2015
DOI: 10.1038/srep13554
|View full text |Cite
|
Sign up to set email alerts
|

Copper induced oxidative stresses, antioxidant responses and phytoremediation potential of Moso bamboo (Phyllostachys pubescens)

Abstract: Moso bamboo is recognized as phytoremediation plant due to production of huge biomass and high tolerance in stressed environment. Hydroponics and pot experiments were conducted to investigate mechanism of copper tolerance and to evaluate copper accumulation capacity of Moso bamboo. In hydroponics experiment there was non significant variation in MDA contents of leaves compared with control. SOD and POD initially indicated enhancing trend with application of 5 μM Cu and then decreased consistently with applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 35 publications
(38 reference statements)
5
106
0
7
Order By: Relevance
“…also reported an increase in the uptake of trace elements in the aerial parts of alfalfa after the application of sheep manure. The uptake of Cu in shoots is low compared to the other elements because it is the least available fraction in soil40.…”
Section: Resultsmentioning
confidence: 99%
“…also reported an increase in the uptake of trace elements in the aerial parts of alfalfa after the application of sheep manure. The uptake of Cu in shoots is low compared to the other elements because it is the least available fraction in soil40.…”
Section: Resultsmentioning
confidence: 99%
“…45 Chen et al, indicated that moso bamboo (Phyllostachys pubescens) can increase the activity of POD to protect it from oxidative damage induced by Cu toxicity, but high Cu stress has caused a large amount of reactive oxygen species which inhibited enzyme activity. 46 Glutathione S-transferases (GSTs) are ubiquitous enzymes that play key roles in detoxifying oxidative-stress metabolites. 47 Khatun et al 48 reported that GST activity in Withania somnifera leaves was increased in the presence of Cu when compared to control plants, indicating that antioxidant enzymes played an important role in protecting the plant from Cu toxicity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Cu is one of these metals, although it is an essential micronutrient for normal plant growth and development, which can impair and damage plant growth when exceeding the optimal concentration12. Various physical and chemical technologies have been developed to remediate soils contaminated with metals, and phytoremediation is becoming increasingly popular because of its economic, energy-efficient, and environmentally friendly features3.…”
mentioning
confidence: 99%